2015
DOI: 10.18806/tesl.v32i2.1205
|View full text |Cite
|
Sign up to set email alerts
|

Request Strategies in Professional E-mail Correspondence: Insights from the United States Workplace

Abstract: Despite growing interest in the rhetorical features of e-mail correspondence, this is the first study to examine the request strategies in e-mails written by native English-speaking professionals from a variety of industries in the United States.This study uses Blum-Kulka, House, and Kasper's (1989)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 34 publications
(37 reference statements)
3
23
0
Order By: Relevance
“…This observation is somewhat in line with findings from the studies on requestive strategies in email writing (Leopold, 2015;Zhu, 2012), which demonstrated that less-proficient English learners tended to use more direct requests and fewer mitigation devices. As shown in the examples above, nearly all the bundles at CELPIP Level 4 are either need-statements or want-statements, while the examples from CELPIP Levels 7 and 10 have slightly more expectation statements (I hope you will or I am hoping for).…”
Section: Stance Bundlessupporting
confidence: 87%
“…This observation is somewhat in line with findings from the studies on requestive strategies in email writing (Leopold, 2015;Zhu, 2012), which demonstrated that less-proficient English learners tended to use more direct requests and fewer mitigation devices. As shown in the examples above, nearly all the bundles at CELPIP Level 4 are either need-statements or want-statements, while the examples from CELPIP Levels 7 and 10 have slightly more expectation statements (I hope you will or I am hoping for).…”
Section: Stance Bundlessupporting
confidence: 87%
“…As Blum-Kulka, Kasper and House (1989) state, the head act "is the core of the request sequence" (p.275). Many studies such as Leopold (2015), Ross (2018) and Kong (2006) have used this notion of a head act to analyze requests in two parts: the request, and supporting moves. This approach allows researchers to investigate what the actual request is and what requesters add to the request to make it less threatening.…”
Section: Cross Cultural Speech Act Realization Projectmentioning
confidence: 99%
“…The ability to participate in this critical component of work is just as important as being able to complete required tasks in order to be successful at work (HOLMES, 2005). Requests -when a speaker wants a hearer to complete an action or share information -are necessary in the workplace (HO, 2018) but the imposing nature of requests may make them difficult to form (LEOPOLD, 2015) (YATES, 2010b). E-mails that are primarily sent to make a request, also called request e-mails, have been reported as intimidating for some employees in a new work setting (LEOPOLD, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a growing body of work on workplace emails, examining both structural and pragmatic aspects, such as politeness and power relations (e.g. Gimenez 2006, Waldvogel 2007, Gilbert 2012, De Felice 2013, Prabhakaran and Rambow 2013, Leopold 2015, McKeown and Zhang 2015, Kim and Lee 2017. The work presented in this paper is a contribution to this field.…”
Section: Background: Workplace Discourse and Corpus Pragmatics Politementioning
confidence: 99%